My cousin Vinny [videorecording (DVD)] - Lynn, Jonathan; Pesci, Joe; Macchio, Ralph, 1961-; Tomei, Marisa; Whitfield, Mitchell, 1969-; Smith, Lane, 1936-2005; Pendleton, Austin; Chaykin, Maury; McGill, Bruce, 1950-; Gwynne, Fred (20th Century Fox Home Entertainment, 2009)
Two carefree pals (Macchio and Whitfield) traveling through Alabama are mistakenly arrested, and charged with murder. Fortunately, Vincent Gambini (Pesci) is the cousin of one of them and he is a lawyer. Vinny is a former auto mechanic from Brooklyn who just passed his bar exam after his sixth try and has never been in court. When cousin Vinny arrives with his leather-clad girlfriend (Tomei) to handle his first case, it's a real shock - for both Vinny and the Deep South.